2021
DOI: 10.3389/fmed.2021.812010
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Psoriasis Following COVID-19 Vaccination: Report From a Single Center

Abstract: The temporal association had been reported between vaccination and exacerbation of psoriasis, and episodes of psoriasis flare-up have recently been attributed to COVID-19 vaccines. We recruited 32 unimmunized controls and 51 vaccinated psoriasis patients, 49 of whom were under biological therapy, with regular clinic visits receiving a total of 63 shots of vaccines, including 30 doses of Moderna mRNA-1273 and 33 doses of AstraZeneca-Oxford AZD1222. Fifteen episodes of exacerbation attacked within 9.3 ± 4.3 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 31 publications
2
52
1
Order By: Relevance
“…In the flare group, most patients received mRNA vaccines (28%) [ 8 , 10 12 , 28 , 38 – 58 ], with the BioNTech/Pfizer vaccine (20%) reported more often than the Moderna vaccine (7%), followed by the AstraZeneca vaccine (7%) [ 5 , 10 , 12 , 26 , 38 , 50 , 59 ] and the Sinovac vaccine (1%) [ 41 , 60 ]. Flares were most commonly reported following the second vaccine dose (23%) [ 5 , 10 , 12 , 38 – 44 , 49 51 , 55 , 56 , 58 ], followed by the first vaccine dose (7%) [ 10 12 , 26 , 28 , 38 , 39 , 48 , 50 , 53 , 54 , 59 ], both the first and second doses (2%) [ 38 , 52 ], and the third dose (1%) [ 8 , 39 ]. The onset time in the flare group ranged from 1 day to 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…In the flare group, most patients received mRNA vaccines (28%) [ 8 , 10 12 , 28 , 38 – 58 ], with the BioNTech/Pfizer vaccine (20%) reported more often than the Moderna vaccine (7%), followed by the AstraZeneca vaccine (7%) [ 5 , 10 , 12 , 26 , 38 , 50 , 59 ] and the Sinovac vaccine (1%) [ 41 , 60 ]. Flares were most commonly reported following the second vaccine dose (23%) [ 5 , 10 , 12 , 38 – 44 , 49 51 , 55 , 56 , 58 ], followed by the first vaccine dose (7%) [ 10 12 , 26 , 28 , 38 , 39 , 48 , 50 , 53 , 54 , 59 ], both the first and second doses (2%) [ 38 , 52 ], and the third dose (1%) [ 8 , 39 ]. The onset time in the flare group ranged from 1 day to 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…We found that while < 1% of patients reported psoriatic reactions in association with COVID-19 vaccination, occurring 5.0 days after vaccination, patients with past histories of psoriasis were 56 times more likely to report psoriatic rashes. Psoriatic flares in response to the COVID-19 vaccine were reported in case reports [ 9 14 ], and in some larger studies [ 1 , 15 ]. For example, in a study of patients with known history of psoriasis (51 vaccinated and 32 not vaccinated against COVID-19) [ 15 ], vaccinated versus unvaccinated patients were almost eight times more likely to experience psoriasis flares ( p = 0.047), at mean 9.3 ± 4.3 days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriatic flares in response to the COVID-19 vaccine were reported in case reports [ 9 14 ], and in some larger studies [ 1 , 15 ]. For example, in a study of patients with known history of psoriasis (51 vaccinated and 32 not vaccinated against COVID-19) [ 15 ], vaccinated versus unvaccinated patients were almost eight times more likely to experience psoriasis flares ( p = 0.047), at mean 9.3 ± 4.3 days following vaccination. In a registry-based study of 414 cases of cutaneous reactions to COVID-19 vaccines [ 1 ], 22.2% (2/9) of patients with history of psoriasis experienced a flare after vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New onset or exacerbations of psoriasis following vaccination have been described in other different types of vaccines, including influenza, Bacillus Calmette-Guerin, tetanus-diphtheria, and pneumococcal polysaccharide vaccines. 4 Recently, new onset or exacerbations of psoriasis associated with COVID-19 vaccines have been reported, including guttate psoriasis and acute generalized pustular psoriasis. 5 Wei et al 1 reported six patients who experienced an exacerbation of known psoriasis and one patient with new-onset psoriasis following COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%